K tipologii nerezul'tativnogo perfekta - Plungjan, Vladimir Aleksandrovič (Slavistična revija, 2018)
This article approaches the intricate grammatical semantics of the periphrastic perfect form in Old Church Slavonic (consistitng of the l-participle and present-tense forms of the auxiliary byti 'be'). Typical uses of this form are discussed in detail; the main objective of the article is to assess the resulting "semantic portrait" of the OCS perfect from a cross-linguistic perspective. It is argued that contrary to typological expectations, the role of the resultative component in the semantics of the OCS perfect is minor (if it exists at all).
Keywords: gramatikalizacija; perfekt; rezultativ; skladnja; stara cerkvena slovanščina